ANALISIS PERLAKUAN AKUNTANSI SEKTOR PUBLIK TERHADAP PENDAPATAN DAN BELANJA DAERAH PADA BADAN PENDAPATAN DAERAH (BAPENDA) KABUPATEN KOLAKA - Dwiningsih, Epita (Jurnal Akuntansi Kompetif, 2024)
This research was conducted by Epita Dwiningsih with NIM 191811091 with the title "Analysis of Public Sector Treatment of Regional Income and Expenditure at the Regional Revenue Agency (Bapenda) of Kolaka Regency" thesis of the Accounting Study Program, Faculty of Social and Economic Sciences under the guidance of Mrs. Sasmita Nabila Syahrir, S.E., M.Ak., CA, ACPA as supervisor I and Mr. Surianto Ilham, S.E., M.Acc., Ak., CA as supervisor II. Equivalent to Government Regulation Number 71 of 2010, the implementation of the research is to study and find out how regional income and expenditure are handled by the public accounting sector at the Regional Revenue Agency (BAPENDA) of Kolaka Regency. The methodology of this research is qualitative. In collecting research data, documentation, interviews, and observation methods are used. The results of the study show that in general the accounting treatment of the Kolaka Bapenda public sector based on Government Regulation Number 71 of 2010 includes indicators of measurement and assessment, recognition, and disclosure of income and expenditure in accordance with these provisions. Meanwhile, Bapenda also revealed that financial management has been in accordance with related provisions, including budget provisions and management of income and expenditure in accordance with Government Regulation Number 71 of 2010 concerning Accrual-Based Government Accounting Standards, based on indicators of accountability, transparency, and public responsibility